EXPLORING MOBILE APPLICATION AND THEIR USAGE IN ENGLISH LANGUAGE LEARNING - Natalia Anggrarini; Ida Yulianawati (Universitas Wiralodra, 2020)
The digital era is undeniable. Communication all over the world runs with the involvement of digital devices. For widespread information, mobile phones such as smartphones play an essential role in learning media, especially in learning English. In learning English as a foreign language, smartphones provide a variety of features to support the learning process. These potential features benefit the students so they can help themselves in improving their ability, especially in the English language. This study explored the kind of mobile application suggested by the teachers to help their students learn English. By conducting a case study, this study covered a variety of mobile applications and their use in the learning activity. About eight teachers from different senior high schools in Indramayu participated in this study. A questionnaire were distributed to the participants to collect the data; then, it was analyzed qualitatively.